Efeito da carbonatação acelerada em painéis de cimento-madeira produzidos com rejeito de minério de ferro - Penha, Eliziane Denize de Castro (2024)
The high volume of waste generated by iron ore processing represents a major environmental challenge. The collapse of the tailings dams in Mariana-MG and Brumadinho-MG highlighted the risks involved in this waste storage model. This study evaluated the physical, mechanical, and thermal performance of wood-cement panels produced with Pinus oocarpa particles, Portland cement CPV-ARI, calcium chloride as an additive, and varying proportions of iron ore tailings (IOT) as a partial replacement for cement (0%, 10%, 20%, and 30% by weight). The effect of accelerated carbonation curing (AC) was investigated by exposing all treatments to a concentrated CO₂ atmosphere at a pressure of 1.5 kgf/cm² and room temperature for 24 hours. The pine particles were characterized by their chemical composition and morphology. The pozzolanic activity of the IOT was assessed according to standards NBR 15895 and NBR 5752. The results of the physical and mechanical properties of the panels were compared with BISON process specifications. The chemical composition of the panels was determined through thermogravimetric analysis and energy-dispersive X-ray spectroscopy (EDS). The results demonstrated that the partial replacement of cement by IOT and the use of AC had a significant effect on most of the studied properties (p<0.05). For the carbonated panels, a reduction in thickness swelling (–15%) and water absorption (–10%) was observed, along with a significant improvement in mechanical properties (~+40%). The interaction between IOT content and ACC was significant only for the mechanical properties (p<0.05). The data indicates a trend of increased strength with the application of AC, a more pronounced effect in panels with higher IOT content. All treatments met the commercial requirements for thickness swelling after 2 h and 24 h, and achieved satisfactory values for the modulus of elasticity (MOE) after AC. For the modulus of rupture (MOR), only the treatment with 30% IOT subjected to AC reached a value above 9 MPa, the minimum requirement defined by BISON. The results suggest the feasibility of using IOT in combination with cement to produce wood- cement panels. On a large scale, the use of IOT in civil construction promotes safer waste disposal, adds value, and reduces production costs.